Menafsir al-Qur’an di Era Digital: Lokalitas, Vernakularisasi, dan Kelisanan pada Pengajian Gus Mus Channel - Cahyani, Nadia Saphira (Contemporary Quran, 2023)
The Mustofa Bisri Channel's usage of YouTube to study tafsir al-Ibrīz represents a substantial shift from traditional teaching techniques. This phenomenon demonstrates a shift from traditional educational techniques to the use of modern technology, particularly social media, to convey religious knowledge. Mustofa Bisri, better known as Gus Mus, uses vernacularization to provide explanations for current situations. This study focuses on how social media promotes conversation between historical texts and present realities. This study examines vernacularization in tafsir al-Ibrīzsessions, including oral interpretation and its impact on comprehension. The Mustofa Bisri Channel's usage of YouTube to study tafsir al-Ibrīz represents a substantial shift from traditional teaching techniques. The authority of a traditional scholar, such as Gus Mus, provides a counter-narrative to less experienced ustaz, indicating pesantren's metamorphosis in the face of modern challenges. This qualitative study employs YouTube content analysis to investigate how local discourse is addressed in spoken interpretations, as well as how oral qualities influence the meaning and relevance of Quranic teachings. Tafsir al-Ibrīz sessions on YouTube demonstrate vernacularization by the use of local language and replies to modern challenges, increasing understanding of Quranic studies. The characteristics of oral interpretation, including the use of conservative language and situational meaning, as well as audience engagement, illustrate how Gus Mus adapts to modernity while preserving the diverse traditions of pesantren teaching.